If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + -12g = -71 Solving -11 + -12g = -71 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -12g = -71 + 11 Combine like terms: -11 + 11 = 0 0 + -12g = -71 + 11 -12g = -71 + 11 Combine like terms: -71 + 11 = -60 -12g = -60 Divide each side by '-12'. g = 5 Simplifying g = 5
| 9(4-s)=10+45 | | 2(2)+3x=24 | | 40(n)=324 | | 34-8x=16+10x | | Y^2-2y+5-8y+10=0 | | 5(h-2)-6(h+1)= | | x+17+2x+1=90 | | 3(n)=210 | | -165=13a | | 17(b-4)= | | 200=x^3+4x^2+4x | | X-2=11/24 | | 22x-3=20+10x | | F/10-11=9 | | 18=9x-7 | | L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 | | 7x-7*2=49 | | y-5=-5.2(x+4) | | 3(n)=1200 | | 6(-9-5x)=-264 | | 7n-3n=4 | | -12=1/8x | | 1(x)=8(40) | | 130=16t*t+27t |